COMPARISON OF ANTIMALARIA DRUGS IN LIBYAN ESSENTIAL DRUG LIST WITH THE NEW ANTIMALARIA DRUGS (ARTIMISININ AND ITS DERIVATIVES) WARRANTS THEIR ADDITION TO THE LIST - LAILA M. KAFU (International Journal of Pharma and Bio Sciences, 2014)
Malaria is the most serious protozoa disease, although it is not endemic in north Africa especially in Libya .Travellers to malarias areas risk infection, the risk can be greatly reduced by taking chemo-prophylactic drugs, however drug resistant plasmodium falciparum is an increasing problem in many parts of the world especially African and some Asian countries. Travellers to endemic countries are at risk to be infected. In African countries with the increasing levels of chloroquine resistance coupled with fears of toxicity and decreased efficacy for sulfadoxine/pyrimithamine (those drugs are included in the Libyan essential drug list); there is an urgent need for an effective and safe alternative to above named drugs. Artemisinin and its derivatives presently showed no cross-resistance with the known anti malarials and as such are important for treating severe infested malaria areas with multidrug resistance also can be administered in combination with other antimalarial drugs. In case of treatment, the Antimalarial activities of Artemisinin and its derivatives are extremely rapid; most patients show clinical improvement within 1-3 days after treatment the recrudescence rate is high even when these drugs are used as monotherepy. In conclusion: This study demonstrates the advantage of artemisinin and its derivatives as anti malarial drugs and the importance there selection and addition to the Libyan Essential drug list.